The space of economic and cultural capital: a latent class analysis for Germany - Waitkus, Nora; Groh-Samberg, Olaf (Empirical investigations of social space, 2020)
Bourdieu’s concept of the social space is a powerful tool for analyzing social inequality in contemporary societies (Bourdieu 1984). His theory combines a structural dimension of various types of resources - called capitals - with a theory of social and cultural practices. As a relational approach, it refers to the relative differences of resources (here: capitals) and elements of cultural practices between individuals or social groups, rather than the absolute level of resources or substantial forms of cultural practices. Bourdieu’s central argument is that the structural dimension of the social space is homologous to the system of differences and oppositions that underlie and structure the social and cultural practices, i.e., the space of lifestyles. This homology is caused by socialization effects which are inherent to the processes of attaining and reproducing various forms of capitals by individuals or families. This theoretical framework allows for a dynamic understanding of social classes: Social classes can be understood as groups of individuals which share similar experiences of acquiring and reproducing certain sets of capitals, via both family socialization and status attainment processes over the life course.